Helix 8 is the essential structural motif of mechanosensitive GPCRs - Erdogmus, Serap; Storch, Ursula; Danner, Laura; Becker, Jasmin; Winter, Michaela Maria; Ziegler, Nicole; Wirth, Angela; Offermanns, Stefan; Hoffmann, Carsten; Gudermann, Thomas; Schnitzler, Michael (Nature Communications, 2019)
GPCRs are versatile cellular sensors for chemical stimuli but the molecular mechanisms underlying mechanically induced GPCR activation have remained elusive. Here authors identify the C-terminal helix 8 (H8) as the essential structural motif endowing H1R and other GPCRs with mechanosensitivity.
Gesehen am 13.05.2020